Are married immigrant women secondary workers? - Ana Ferrer (IZA World of Labor, 2015)
What is the role of married women in immigrant households? Their contribution to the labor market has traditionally been considered of secondary importance and studied in the framework of temporary attachment to the labor force to support the household around the time of arrival. But this role has changed. Evidence from major immigrant-receiving countries suggests that married immigrant women make labor supply decisions similar to those recently observed for native-born married women, who are guided by their own opportunities in the labor market rather than by their spouses' employment trajectories.
Keywords: J24; 330; skilled immigrants; skill assimilation; labor market outcomes of immigrant women